Level of knowledge and preventive practice in the population affected with dengue, Ferreñafe, 2019 - Bravo Rodriguez, Pamela del Carmen (2021)
Objective: Identify the relationship between the level of knowledge and preventive practice in people affected with dengue, Ferreñafe 2019. Method: Quantitative study with descriptive correlational design. The sample consisted of 252 people affected with the dengue virus, the sampling was for convenience, taking into account the inclusion and exclusion criteria. The survey was used as a technique and as a tool a questionnaire to measure the level of knowledge and a checklist for preventive practice prepared by García, Torres and Tangoa, instruments were validated at the local level with the Richardson's Kuder method having 0.890 and 0.820 reliability respectively. Main results: Yes, there is a perfect and directly proportional positive relationship with bilateral significance (rs = 0.858, p = 0.000) between the level of knowledge and preventive practice in the dengue-affected population. So, the null hypothesis is rejected. General conclusion: The higher the level of knowledge presented by the person affected by dengue, the preventive practice that is developed is very good or vice versa. Descriptors: Dengue (D003715), Knowledge (D019359), Disease prevention (50219)